Clipping the Wings of Glioblastoma: Modulation of WNT as a Novel Therapeutic Strategy. Issue 5 (11th March 2016) - Suwala, Abigail K.; Hanaford, Allison; Kahlert, Ulf D.; Maciaczyk, Jaroslaw
Abstract : Glioblastoma (GBM) is the most malignant brain tumor and has a dismal prognosis. Aberrant WNT signaling is known to promote glioma cell growth and dissemination and resistance to conventional radio- and chemotherapy. Moreover, a population of cancer stem-like cells that promote glioma growth and recurrence are strongly dependent on WNT signaling. Here, we discuss the role and mechanisms of aberrant canonical and noncanonical WNT signaling in GBM. We present current clinical approaches aimed at modulating WNT activity and evaluate their clinical perspective as a novel treatment option for GBM.